Protective Effects of Rosa Canina L Fruit Extracts on Renal Disturbances Induced by Reperfusion Injury in Rats (Iranian Journal of Kidney Diseases, 2013)
Introduction. This study aimed to investigate the effects of Rosa canina L fruit extracts on histological damages, oxidative stress, and functional disturbances induced by bilateral renal ischemia and reperfusion. Materials and Methods. Ischemia and reperfusion were induced on the kidneys of anesthetized male Sprague-Dawley rats. The rats in the reperfusion and Rosa canina groups were administered extract solvent and Rosa canina extract, respectively. In addition, in the sham group, surgery was done without ischemia. In the last 6 hours of the reperfusion period, urine sample were collected using metabolic cage and at the end of this period, blood samples were taken from the descending aorta. The kidney tissues were collected and subjected to microscopic study for histological damages, while oxidative stress was measured by determining malondialdehyde and ferric reducing/antioxidant power levels. Results. The comparison between the reperfusion and sham groups indicated reductions in creatinine clearance, absolute excretion of potassium, urine osmilarity, and increase in absolute excretion of sodium in the reperfusion group. These changes were less pronounced with Rosa canina fruit extract. In addition, blood creatinine and urea concentrations which increased in the reperfusion group, were significantly lower in the Rosa canina group. In this group, the degree of histological damages and the level of malondialdehyde were lower than the reperfusion group, while ferric reducing/antioxidant power level was significantly higher. Conclusions. The findings of this study showed that Rosa canina fruit extract possesses protective effects against kidney function disturbances, oxidative stress, and histological damages.